Ecological Recycling of a Bio‐Based Catalyst for Cu Click Reaction: a New Strategy for a Greener Sustainable Catalysis. Issue 7 (20th May 2016) - Clavé, G.; Garoux, L.; Boulanger, C.; Hesemann, P.; Grison, C.
Abstract: We report the elaboration of novel bio‐sourced ecocatalysts for the Cu catalyzed azide‐alkyne cycloaddition reaction (CuAAC). Ecocatalysis is based on the recycling of metals issued from rhizofiltration of metal rich effluents, and an innovative chemical valorization of the subsequent biomass in the field of catalysis. Taking advantage of the remarkable ability of Eichhornia crassipes to accumulate Cu(II) into its roots, these can be directly used for the preparation of copper containing ecocatalysts, called EcoCu, which appear as highly active catalysts in the CuAAC reaction. Furthermore, the recycling of Cu from the reaction mixture via E. crassipes is carried out ecologically. The resulting EcoCu2 material displays reusability for the CuAAC reaction under identical experimental conditions without a loss of its catalytic activity. Abstract : Ecological recycling of effluents rich in Cu through rhizofiltration constituted the raw material for efficient catalyzed CuAAC click reaction.